The PTSD Survival Guide for Teens : Strategies to Overcome Trauma, Build Resilience, and Take Back Your Life. - Raja, Sheela (Instant Help Solutions Ser., 2018)
Teens who've experienced trauma or suffer from post-traumatic stress disorder (PTSD) often struggle to gain the confidence and resilience needed to move forward after their difficult experience. In The PTSD Survival Guide for Teens, trauma specialist Sheela Raja--along with her teen daughter Jaya Ashrafi--offers accessible skills based in cognitive behavioral therapy (CBT), dialectical behavior therapy (DBT), and acceptance and commitment therapy (ACT) to help teens tackle anxiety and avoidance, manage negative emotions, cope with flashbacks and nightmares, and develop trusting, healthy relati.